Fabrication of strengthening treatment method for marine clay - Kamaruddin, Fatin Amirah (2021)
Development of road traffic on marine clay poses a serious problem when this type of soil is being used. In order to solve the problem, the soil would need to be treated to improve its condition. Lime and alkaline activation (AA) are binder techniques that can be used to improve soil strength. However, treating soil with only binder would lead to brittle failure for the soil treatment. Therefore, to improve the mechanical properties of the treated soils to ductile, the inclusion of treated natural coir fibre with randomly distributed soil reinforcement is required. This research is focused on investigating the performance of treated coir fibre with two different stabilizers by using lime and alkaline activation subjected to static and dynamic loading. The surface of the fibre was treated with calcium chloride (CaCl2), which was proven effective in increasing the tensile strength and improving the fibre adhesion. For the laboratory work, 165 samples (for main tests-range of 3 duplicate tests each) were tested according to the British Standard (BS) and American Society for Testing and Materials (ASTM). The specimens were prepared by using the remoulded method and were cured for 7, 28 and 90 day curing periods before the testing was conducted. There were seven major tests carried out on untreated soils, treated soil with lime, and treated soil with alkaline activation, which were physical properties, compaction test, unconfined compressive strength (UCS) test, flexural strength (FS) test, indirect tensile strength test (ITS), consolidated isotropic undrained (CIU) test (static load), and dynamic loading test. For the determination of soil behaviour on the CIU test, two types of parameters, which are maximum deviator stress and axial strain, were obtained and analyzed. The results were then used for the further investigation in the dynamic loading test. Besides that, for fundamental research on dynamic loading, the main parameters were comprised of the damping ratio (D) and shear modulus (G). The parameters were defined based on the equation from the stress-strain curve that is generated through AutoCAD software to calculate the area that is produced by the hysteresis loop. The results of this study show that for a 7 day curing period up to a 90 day curing period, the compressive strength, flexural strength, and indirect tensile strength tests of treated soil with alkaline activation showed higher increments than treated soil with lime. The increments observed were up to 46 % and 71 % for the unconfined compressive strength test, 35 % and 81 % for flexural strength, and 53 % and 69 % for the indirect tensile strength test for both treated lime and alkaline activation, respectively. Other than that, the strength of the increment can be summarized up to 87 % and 98 % for both treated with lime and alkaline activation compared to the untreated soil specimens for the three tests. Moreover, for the dynamic loading test, it can be concluded that the value of G was increased with the addition of stabilizer in the soil, which can be interpreted by the decrease of strength as the curing periods increase between 60 to 40 kPa (lime) and 760 kPa to 210 kPa (AA). Meanwhile, for the value of D, the result showed a decrease as the curing periods increase from 23 % to 32 %, 15 % to 25 % and 5 % to 9 % for untreated soil, treated soil with lime, and treated soil with alkaline activation, respectively. These results show that the addition of the stabilizer to the soil had different effects on the dynamic loading parameter behaviour. The test can be confirmed with the field emission scanning electron microscopy (FESEM) and energy-dispersive X-ray spectroscopy (EDX) tests where there is an interaction between treated soil and fibre as filler, thus strengthening the soil. Therefore, it can be concluded that this research is important as it contributes to proving that the inclusion of fibre as one of the admixtures in the stabilizer not only helps in improving the mechanical interactions between the soil, fibre and the stabilizer but it also results in increasing the performance of the soils as it could be used for the development of light traffic loading in the area of marine clay.